STUDI KAUSALITAS MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BANK MUAMALAT KCU FATMAWATI - Sutoro, Moh.; Darmadi, Darmadi (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The aim of this research is to determine the influence of work motivation and discipline on employee performance at PT Bank Muamalat KCU Fatmawati partially and simultaneously. The method used is descriptive quantitative. The sampling technique uses a saturated sampling technique from a population of 60 as samples. The method used to test and analyze the influence partially and simultaneously uses hypothesis testing (t test and f test). This study investigates the significant impact of work discipline and work motivation on employee performance. Data analysis reveals that work discipline has a substantial influence on performance, with a contribution value of 0.933. This suggests that adherence to rules and punctuality play a crucial role in enhancing employee output, as supported by reinforcement theory and time management principles. Additionally, work motivation shows a significant effect on performance, with a contribution value of 0.672, highlighting the importance of intrinsic motivation factors, such as achievement and recognition, in driving employees to excel. The findings underscore the need for a comprehensive approach in performance management, emphasizing both the establishment of strong disciplinary practices and the cultivation of high motivation levels to optimize employee performance.